Managing diversity : expert solutions to everyday challenges. - Harvard Business School. Press (Boston, Mass. : Harvard Business Press, 2009)
This title teaches managers how to recruit a diverse team; foster an inclusive environment by replacing common misperceptions with facts; handle diversity-related conflict; and how to tap the business value generated by the team's diversity.
Includes bibliographical references (pages 95-105).
Print version record.
Keywords: Diversity in the workplace; Diversity in the workplace; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books